Epidemiology, risk factors, outcomes, and role of Serpin A3 as a biomarker for transition of acute kidney injury to chronic kidney disease in critically ill patients - Marwa K. Khairallah; Asmaa A. Gaber; Mohammed H. Maghraby; Marwa A. Dahpy; Simran Singh Parmer; Mohammed H. Mostafa (SpringerOpen, 2024)
Abstract Background Several studies have suggested a causal link between acute kidney injury and the consequent development of chronic kidney disease. The severity, frequency, and duration of acute injury are key factors in this process. Aims This study aimed to determine the epidemiology and outcomes of AKI to CKD transition in critically ill adult patients and to study the role of Serpin-A3 in the early recognition of AKI to CKD transition. Methods In this prospective observational study, a total of 252 patients attending Assiut University Hospitals Critical Care Unit and developed AKI during their stay were recruited. Serum and urinary Serpin A3 were measured by ELISA Kit. Complete blood picture, kidney function tests, urine analysis, serum electrolytes (serum sodium, potassium, calcium, phosphorus, and magnesium), liver function test, coagulation profile, C-reactive protein, 24-h urinary protein or urinary albumin/creatinine ratio, abdominal ultrasound were assessed for all the recruited participants. Follow-up was done for three consecutive months and after 3 months using serum creatinine, BUN, and serum potassium. Results It was found that old age is a risk factor for CKD following AKI, i.e., with 1-year increase in the patient's age, there was 3% increase in the chance of transition. Significant association was found between rate of comorbidity and transition status. Also, cases with either infection or IV radio contrast exposure were 2.8 and 6.5 times more liable for transition. Cases with transition in this study had significantly higher renal function parameters. Higher median levels of Serpin A3 either serum or urinary was reported in transition patients. Improvement was reported in two-third of those without transition, and higher mortality rate was recorded in those without transition. Conclusion The frequency of transition was 20%. Older age, male gender, cardiac and CVS disease, the presence of infection, higher BUN and creatinine level, higher median K and PO4 levels, and higher median levels of Serpin A3 are risk factors for transition from AKI to CKD.